PENGEMBANGAN MEDIA PEMBELAJARAN VISUAL INTERAKTIF WORDWALL UNTUK MENINGKATKAN PEMAHAMAN BAHASA DALAM MATERI DESKRIPTIF PADA SISWA LEMAH INTELEKTUAL - Fika Dia Pramesti; Afrinar Pramitasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to (1) describe the results of the needs analysis for interactive visual learning media required to improve language comprehension among seventh-grade junior high school students with intellectual disabilities, (2) design interactive visual learning media based on Wordwall that are aligned with the characteristics, abilities, and learning needs of students with intellectual disabilities, and (3) develop feasible interactive visual learning media to enhance students' language comprehension in descriptive text materials. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research subjects included three expert validators (media, material, and language experts) and seventh-grade students of SMP Negeri 4 Pekalongan in the 2026/2027 academic year. Data were collected through observation, interviews, questionnaires, tests, and documentation. The results indicated that the developed Wordwall-based interactive visual learning media were feasible for use, with an average expert validation score of 79.17%, categorized as fairly valid. The limited trial showed an increase in the average pre-test score from 77.77 to 85.55 in the post-test, while the field trial demonstrated an improvement from 72.67 to 85.67. In addition, students showed positive responses toward the learning media, as it increased their motivation, participation, and ease of understanding descriptive text materials through interactive visual activities. Therefore, the Wordwall-based interactive visual learning media can serve as an effective alternative learning medium for improving language comprehension among seventh-grade students with intellectual disabilities.